Pengaruh Dosis Trikokompos terhadap Bobot, Diameter dan Kadar Gula Melon (Cucumis melo) - Luluk Syahr Banu; Siti M. Sholihah; Faisal Gymnastiar (JURNAL PERTANIAN, 2025)
Melon is a fruit commonly served as a dessert at various dining events. Its nutritional content and pleasant taste make it popular among consumers. Due to high market demand, melon production continues to increase; however, one of the problems in production is the excessive use of inorganic fertilizers. This study aimed to determine the effect of trichocompost dosage on fruit weight, diameter, and sugar content of melon (Cucumis melo), as well as to examine the presence of interaction between the treatments. The research was conducted at the Ragunan Agro-education Tourism area and the Laboratory of the Faculty of Agriculture, Universitas Respati Indonesia, from March to July 2025. The experiment was carried out in the field using a factorial Completely Randomized Design (CRD). The study consisted of two treatment factors. The first factor was trichocompost dosage with four levels: P0 = without trichocompost fertilizer, P1 = 500 g trichocompost, P2 = 1,000 g trichocompost, and P3 = 1,500 g trichocompost. The second factor was melon variety, consisting of V1 = Sweet Net variety and V2 = Rock Melon variety. Each treatment was replicated three times. The observed variables included fruit weight (g), fruit diameter (mm), and sugar content (°Brix). The results showed that trichocompost dosage significantly affected fruit weight and diameter but had no significant effect on sugar content. The melon variety factor had no significant effect on all observed variables, and no interaction was found among the treatments for all variables.